REDUCTION OF ENGLISH NOMINAL GROUP EXPERIENTIAL STRUCTURE IN INDONESIAN SUBTITLE: BECOMING NEW ENTITY? - Romel Noverino; M. R. Nababan; Riyadi Santosa; Djatmika Djatmika (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Reduction in subtitling is inevitable due to technical rules of time and space as well as synchronization, i.e. displaying subtitle when the utterance/dialogue is spoken. Consequently, reduction leads to the loss of meaning incorporated into the subtitle. Reduction takes place within linguistic unit, such as word, group of words, even clause/sentence. Under the scrutiny of experiential dimension within ideational metafunction of Systemic Functional Linguistics, this qualitative study article discusses the results of a study on how far reduction of English Nominal Group (NG) elements as experiential structure has contributed to alteration of entity expression in the Indonesian subtitle of The Kingdom (2007), of which the objective data were collected by way of purposive sampling. The results show that reduction of English NG experiential structure set new expression of entity and even reduction of the NG main element, Thing, resulted in the loss of entity in the subtitle.